Breakfast on a dragon's tail and other book bites - Springett, Martin (Fitzhenry & Whiteside, 2011)
An interactive collection of illustrated book covers for thirteen different storybooks along with the story's beginning), but the reader invited to allow their imagination to take over and write the ending